Are face masks a partisan issue during the COVID‐19 pandemic? Differentiating political ideology and political party affiliation. (21st September 2021) - Howard, Matt C.
Abstract : Popular press articles have asserted that those with certain political orientations are less likely to wear face masks during the COVID‐19 pandemic. We propose that this relation is due to differential information shared by political parties rather than values associated with face mask wearing. We further propose that, when assessed together, political party affiliation (e.g., Republican, Democrat) but not political ideology (e.g., conservative, liberal) predicts face mask wearing, and this effect is mediated by perceptions of efficacy doubts but not perceptions that face masks infringe upon the wearer's independence. We performed a three‐wave, time‐separated survey study with 226 participants. Each proposal was supported. When assessed together, political party affiliation but not political ideology significantly predicted face mask wearing, and a significant indirect effect was observed via perceptions of efficacy doubts but not independence. Our results support that face mask wearing is a unique preventative action, which should be understood using political theory.